Two-warehouse inventory model with non-instantaneously deteriorating items, stock-dependent demand, shortages and inflation. Issue 2 (2nd April 2016) - Palanivel, M.; Sundararajan, R.; Uthayakumar, R.
Abstract : In this paper, a two-warehouse economic order quantity (EOQ) model for non-instantaneously deteriorating items with stock-dependent demand under the effects of inflation and the time value of money is presented. Also in this model, shortages are allowed and partially backlogged. The backlogging rate is dependent on the waiting time for the next replenishment. The objective of this model is to minimize the total inventory cost of the retailer by finding the optimal intervals and the optimal order quantity. An algorithm is designed to find the optimum solution of the proposed model. Numerical examples are given to demonstrate the results. Sensitivity analysis of the model with respect to several system parameters has been carried out and some managerial inferences are obtained.